2003
DOI: 10.1111/j.1741-3729.2003.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Assortative Mating Among Adult Children of Alcoholics and Alcoholics*

Abstract: Relations between parental alcoholism, self-alcoholism, and partner-alcoholism were examined in a nonclinical, non-self-identified sample of 128 married and engaged young couples. Couples were recruited to participate in a longitudinal study of close relationships. They were assessed using three alcoholism questionnaires that included reports of parent-, partner-, and self-alcohol use. Participants were predominantly White and well educated. Cross-sectional analyses indicated that alcoholics tend to marry othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…Evidence for a relationship between problem behavior in individuals and in the first-degree relatives of their partners may provide support for phenotypic preference, by indicating that individuals with problem behavior select partners at higher-risk for problem behavior by virtue of family history (i.e., secondary assortative mating; Cloninge et al, 1979;McLeod, 1995). This relationship could also support social homogamy, given that problem behavior covaries with social experiences, including having an alcoholic parent (e.g., Olmsted et al, 2003;Windle, 1997). Some research on ACOAs has suggested a significant relationship between a family history of alcohol dependence and marriage to an alcoholic (e.g., Black et al, 1986;Hall et al, 1983b;Kerr and Hill, 1992;Schuckit et al, 1994).…”
Section: Children Of Alcoholicsmentioning
confidence: 89%
See 3 more Smart Citations
“…Evidence for a relationship between problem behavior in individuals and in the first-degree relatives of their partners may provide support for phenotypic preference, by indicating that individuals with problem behavior select partners at higher-risk for problem behavior by virtue of family history (i.e., secondary assortative mating; Cloninge et al, 1979;McLeod, 1995). This relationship could also support social homogamy, given that problem behavior covaries with social experiences, including having an alcoholic parent (e.g., Olmsted et al, 2003;Windle, 1997). Some research on ACOAs has suggested a significant relationship between a family history of alcohol dependence and marriage to an alcoholic (e.g., Black et al, 1986;Hall et al, 1983b;Kerr and Hill, 1992;Schuckit et al, 1994).…”
Section: Children Of Alcoholicsmentioning
confidence: 89%
“…Although several studies have suggested sex differences in assortative mating and behavior contagion (e.g., Galbaud du Fort et al, 1998;Gleiberman et al, 1992;Hall et al, 1983a, b;Haynie et al, 2005;Kim and Capaldi, 2004;McLeod, 1995;Moffitt et al, 2001;Moskalenko et al, 1992;Olmsted et al, 2003;Sakai et al, 2004;Schuckit et al, 1994;Kandel, 1993, 1997), findings have been weakened by methodological limitations (e.g., low power, clinical samples) and have been inconsistent and contradictory across studies. Furthermore, Jacob and Bremer (1986) demonstrated how the failure to account for sex differences in the base rates for substance use and dependence, as well as deficiencies and discrepancies in methodology across studies, lead to erroneous conclusions regarding sex differences in assortative mating.…”
Section: Summary and Evaluation Of Research On Problem Behavior And Rmentioning
confidence: 96%
See 2 more Smart Citations
“…This similarity does not restrict itself solely to attitudes and values, as behavioral patterns also often coincide. The literature on addiction has shown that people who abuse substances or report addictive behaviors are more likely than others to have a long term relationship with someone who has the same type of problematic behavior (Grant et al, 2007;Homish, Leonard, & Cornelius, 2007;Ladd & Petry, 2002;McLeod, 1993a;Olmsted, Crowell, & Waters, 2003;Schuckit et al, 2002;Shaw et al, 2007). Homish and Leonard (2005) showed, for example, that similarity between partners in the level of alcohol consumption was related to greater marital happiness, particularly in young couples.…”
Section: Married Couples In the Offline Worldmentioning
confidence: 99%